Methylation of SSTR4 promoter region in multiple mental health disorders - Zhao, Rongrong; Shi, Huihui; Wang, Yanqiu; Zheng, Shuaiyu; Xu, Yahui (Frontiers in Genetics, 2024)
The existence of a shared genetic basis for mental disorders has long been documented, yet research on whether acquired epigenetic modifications exhibit common alterations across diseases is limited. Previous studies have found that abnormal methylation of cg14631053 at the SSTR4 promoter region mediates the onset of alcohol use disorder. However, whether aberrant methylation of the SSTR4 gene promoter is involved in other mental health disorders remains unclear. In this study, leveraging publicly available data, we identified that changes in methylation of cg14631053 from the SSTR4 promoter region are involved in the development of bipolar disorder and schizophrenia. Furthermore, the direction of methylation changes in the SSTR4 promoter region is disease-specific: hypomethylation is associated with the onset of bipolar disorder and schizophrenia, rather than major depressive disorder. Methylation levels of cg14631053 correlate with chronological age, a correlation that can be disrupted in patients with mental health disorders including schizophrenia and bipolar disorder. In conclusion, SSTR4 promoter methylation may serve as a marker for identifying bipolar disorder and schizophrenia, providing insights into a transdiagnostic mechanism for precision medicine in the future.